Advanced asymmetric supercapacitors based on CNT@Ni(OH)2 core–shell composites and 3D graphene networks1. Issue 38 (14th October 2015) - Yi, Huan; Wang, Huanwen; Jing, Yuting; Peng, Tianquan; Wang, Yiran; Guo, Jiang; He, Qingliang; Guo, Zhanhu; Wang, Xuefeng
<x xml:space="preserve">Abstract</x> Asymmetric supercapacitors with CNT@nickel hydroxide nanosheet composites and 3-D graphene networks demonstrated a high energy density (∼44.0 W h kg−1) and high power density (∼16 kW kg−1) in aqueous KOH electrolyte.